Case report fasciolopsiasis: a first case report from Malaysia - Rohela, M.; Jamaiah, I.; Menon, J.; Rachel, J. (2005)
Fasciolopsiasis is a disease caused by the largest intestinal fluke, Fasciolopsis buski. The disease is endemic in the Far East and Southeast Asia. Human acquires the infection after eating raw freshwater plants contaminated with the infective metacercariae. There has been no report of fasciolopsiasis either in man or in animal in Malaysia. We are reporting the first case of fasciolopsiasis in Malaysia in a 39-year-old female farmer, a native of Sabah (East Malaysia). This patient complained of cough and fever for a duration of two weeks, associated with loss of appetite and loss of weight. She had no history of traveling overseas. Physical examination showed pallor, multiple cervical and inguinal lymph nodes and hepatosplenomegaly. Laboratory investigations showed that she had iron deficiency anemia. There was leukocytosis and a raised ESR. Lymph node biopsy revealed a caseating granuloma. Stool examination was positive for the eggs of Fasciolopsis buski. The eggs measure 140 x 72.5 microm and are operculated. In this case, the patient did not present with symptoms suggestive of any intestinal parasitic infections. Detection of Fasciolopsis buski eggs in the stool was an incidental finding. She was diagnosed as a case of disseminated tuberculosis with fasciolopsiasis and was treated with antituberculosis drugs and praziquantel, respectively.